Effect of climate history on the genetic structure of an Antarctic soil nematode - Jackson, Abigail C.; Leavitt, Steven D.; Porazinska, Dorota; Wall, Diana H.; Powers, Thomas O.; Harris, Timothy S.; Adams, Byron J. (Frontiers in Ecology and Evolution, 2025)
Historical climate disturbances such as glacial cycling and fluctuating stream, lake, and sea levels strongly influence the distribution and evolutionary trajectories of Antarctic terrestrial species. Antarctic invertebrates, including the ubiquitous sentinel nematode species Scottnema lindsayae, are especially sensitive to climate disturbances. We tested hypotheses associated with the historical geographic and population genetic structure of this species as it occurs across the McMurdo Dry Valleys of Antarctica. To reconstruct the influence of climate disturbance and ecological conditions on this species, partial mitochondrial cytochrome c oxidase I gene sequences were analyzed from individual S. lindsayae collected from sites across the McMurdo Dry Valleys reflecting opposing gradients of climate disturbance during the Last Glacial Maximum. We found that populations were strongly demarcated by geomorphic barriers, with distinct haplotypes associated with valleys except among valleys that experienced glacial advance and retreat during the LGM. Our work shows that contemporary populations of these animals are strongly structured by prior climate history and reinforced by subsequent ecological conditions. Such findings can be useful for understanding the processes that shape the distribution and abundance of these ecologically important animals and interpreting long-term monitoring of demographic shifts in response to changing climate trends in the McMurdo Dry Valleys.